Unpacking the Logic of Compliance in Special Education: Contextual Influences on Discipline Racial Disparities in Suburban Schools. Issue 3 (July 2021) - Kramarczuk Voulgarides, Catherine; Aylward, Alexandra; Tefera, Adai; Artiles, Alfredo J.; Alvarado, Sarah L.; Noguera, Pedro
The Individuals with Disabilities Education Act ([IDEA] 2004; IDEA Amendments 1997) is a civil rights–based law designed to protect the rights of students with disabilities in U.S. schools. However, decades after the initial passage of IDEA, racial inequity in special education classifications, placements, and suspensions are evident. In this article, we focus on understanding how racial discipline disparities in special education outcomes relate to IDEA remedies designed to address problem behaviors. We qualitatively examine how educators interpret and respond to citations for racial discipline disproportionality via IDEA at both the district and the school level in a suburban locale. We find that educators interpret the inequity in ways that neutralize the racialized implications of the citation, which in turn affects how they respond to the citation. These interpretations contribute to symbolic and race-evasive IDEA compliance responses. The resulting bureaucratic and organizational structures associated with IDEA implementation become a mechanism through which the visibility of race and racialization processes are erased and muted through acts of policy compliance. Thus, the logic of compliance surrounding IDEA administration serves as a reproductive social force that sustains practices that do not disrupt locally occurring racialized inequities.